Visible light-driven photocatalytic degradation performance for methylene blue with different multi-morphological features of ZnS. Issue 52 (11th May 2016) - Rao, Hanbing; Lu, Zhiwei; Liu, Xin; Ge, Hongwei; Zhang, Zhaoyi; Zou, Ping; He, Hua; Wang, Yanying
Abstract : SEM images of synthesized 3D ZnS microspheres self-assembled with various precursor substances by different hydrothermal synthesis methods: (a) dandelion-ZnS, (b) raspberry-ZnS, (c) ball-ZnS and (d) flower-ZnS. Abstract : In this study, four different sphere structures of zinc sulfide (ZnS) materials, dandelion-ZnS, raspberry-ZnS, ball-ZnS and flower-ZnS, were synthesized via a hydro-thermal method. Afterwards, the photocatalytic performances of the produced ZnS powders were investigated using methylene blue (MB) visible light induced photodegradation. X-ray diffraction (XRD), scanning electronic microscopy (SEM), Brunauer–Emmett–Teller (BET), Fourier transform infrared spectroscopy (FT-IR) and UV-visible diffuse reflectance spectroscopy (UV-vis-DRS) were used for characterization of the as-prepared ZnS powders. The specific surface areas of dandelion-ZnS, raspberry-ZnS, ball-ZnS and flower-ZnS were found to be 112, 119, 5.89 and 37.4 m 2 g −1, respectively. The MB photodegradation by ZnS fitted well with a pseudo-first-order model. The high specific surface areas, unique morphology, porous structures and high hydrophilicity contribute to the photocatalytic abilities of ZnS. However, it shows that ZnS with simple structures has better reusability.